The Composition of Ian Stevenson’s Twenty Cases Suggestive of Reincarnation - Matlock, James G. (Journal of Scientific Exploration, 2024)
Ian Stevenson was trained as a physician and, later, as a psychiatrist. He made significant contributions to biochemistry, psychosomatic medicine, and other areas before turning to parapsychology in mid-career. From the start of his involvement in parapsychology, Stevenson was interested in claims to remember previous lives. As his research with such claims progressed, he became convinced of reincarnation’s potential to shed light on unresolved problems in medicine. This paper describes the background and traces the development of Stevenson’s classic collection of case reports, Twenty Cases Suggestive of Reincarnation, whose first edition appeared in 1966. Stevenson expected his monograph to be recognized as making the important contribution he believed it did and thought that it would lead to public funding for further research on reincarnation. Sixty years on that has yet to happen, perhaps due to Stevenson’s emphasis on the proof-oriented aspects of the cases he reported, to the neglect of other issues that might have connected more easily with mainstream interests, and more directly countered criticisms of his research methodology.